Annual Survey of Governments, 1988: Employment Statistics ([Verlag nicht ermittelbar], 1990)
Federal, state, and local government employment data are provided in this file. Full- and part-time employment, full-time equivalency, and payroll statistics are included. Data are supplied by type of government (federal, state, county, city, township, special district, and school district) and by function. Governmental functions include education (elementary, secondary, and higher education), police and fire protection, financial administration, judicial and legal functions, highways, solid waste management and sewage, libraries, air and water transportation and terminals, state liquor stores, social insurance administration, housing and community development, utilities, public welfare, parks and recreation, health care, transit, and natural resources.